How the use of the International Classification of Functioning, Disability and Health for Children and Youth changed the Individualized Education Programs in Portugal. Issue 5 (4th May 2017) - Silveira-Maia, Mónica; Lopes-dos-Santos, Pedro; Sanches-Ferreira, Manuela
ABSTRACT: Current Portuguese Public Law No. 3/2008 requires the use of the International Classification of Functioning, Health and Disability for Children and Youth (ICF-CY) as a reference framework to guide assessment and intervention procedures for students with additional support needs. This study explores whether the ICF-CY use fostered multidimensional and interrelational descriptions of students' needs, and enhanced the congruence between assessment data and intervention plans. Content analyses were conducted on a total of 198 Individualized Education Programs (IEPs) concerning 99 students. Two IEPs were compared for each student, one delineated before and the other designed after the mandatory ICF-CY usage. An analytic process was conceived to measure operational indicators of multidimensionality, interrelatedness and congruency in the descriptions written in the IEPs. The results indicate that the ICF-CY use has supported more complete portrayals of students' functioning, a broader emphasis on person–environment reciprocal influences, and greater individualised responses, linking goals and strategies to individual and environmental specific circumstances. It had not made an impact on the intervention procedures, namely on regard to multidimensionality and interrelatedness. The integration of the ICF-CY conceptual framework into the IEPs, as a stage of implementation that goes beyond the usage of its taxonomic structure, is discussed.